2022
DOI: 10.3340/jkns.2021.0131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hounsfield Unit Value with Conventional Computed Tomography and Intraoperative Distraction on Postoperative Intervertebral Height Reduction in Patients Following Stand-Alone Anterior Cervical Discectomy and Fusion

Abstract: Objective : The most common complication of anterior cervical discectomy and fusion (ACDF) is cage subsidence and maintenance of disc height affects postoperative clinical outcomes. We considered cage subsidence as an inappropriate indicator for evaluating preservation of disc height. Thus, this study aimed to consider patients with complications such as reduced total disc height compared to that before surgery and evaluate the relevance of several factors before ACDF.Methods : We retrospectively reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Wang et al [ 29 ] reported that lower preoperative HU values of the vertebral are associated with cage subsidence in single-level ACDF. Another study reported that lumbar BMD values were significantly correlated with cervical HU values; moreover, low HU values may lead to postoperative intervertebral height reduction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 29 ] reported that lower preoperative HU values of the vertebral are associated with cage subsidence in single-level ACDF. Another study reported that lumbar BMD values were significantly correlated with cervical HU values; moreover, low HU values may lead to postoperative intervertebral height reduction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that the HU value of the vertebral was closely related to BMD and could evaluate the risk of pedicle screw loosening and cage subsidence in lumbar spine surgery [ 15 18 ]. A few studies have evaluated the association between vertebral body HU value and cage subsidence after anterior cervical discectomy and fusion (ACDF) [ 19 , 20 ]. However, the relationship between the HU value of the vertebral body and TMC subsidence in ACCF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nine of these were retrospective cohort or database studies, and 2 were prospective cohort studies. [6][7][8][9][10][11][12][13][14][15][16] Of the 8 studies that assessed cage migration, 5 found that poor bone stock was associated with the development of this complication. 7,9,10,14, 15 Lee et al calculated Hounsfield units (HUs) based on 6 regions of the cervical spine in a cohort of 40 patients who underwent anterior cervical discectomy and fusion (ACDF) with stand-alone polyether-ether-ketone (PEEK) cages.…”
Section: Radiographic Outcomesmentioning
confidence: 99%
“…The literature currently presents conflicting evidence for many postoperative complications, including rates of cage subsidence, pseudarthrosis, readmission, and reoperation in osteoporotic patients following surgery for cervical spine pathology. [6][7][8][9][10][11][12][13][14][15][16] Thus, the purpose of this review is to systematically gather and analyze current data to create a more comprehensive understanding of how osteoporosis potentially impacts outcomes following surgery for degenerative cervical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the current study, cage subsidence was calculated using a well-validated method of total loss of segmental height as the difference from the postoperative X-ray taken within 1 week after surgery to the most recent follow-up X-ray. 10,[17][18][19][20] The segmental height was calculated on lateral X-ray as the distance from the inferior endplate of the inferior fused vertebral body to the superior endplate of the superior fused vertebral body. Cage subsidence was defined as ≥3 mm loss of segmental height of the fusion, which has been demonstrated as a well validated threshold in previous literature.…”
Section: Cage Subsidence Calculationmentioning
confidence: 99%